Make it burn? Wildfires, disaster aid and presidential approval - Michael Berlemann; Timur Eckmann; Marina Eurich (Hamburg Institute of International Economics (HWWI), 2024)
For governments, the occurrence of natural disasters creates the opportunity to demonstrate their willingness and competence in providing prompt and efficient disaster aid. A number of studies has investigated the political consequences of providing disaster aid by analyzing the effects of such aid on subsequent election results. However, the findings of these studies have not yielded a coherent picture. This paper makes a contribution to the existing literature by employing high-frequency survey data on presidential approval. The combination of this data with wildfire data and information on Federal Emergency Management Agency (FEMA) aid approvals and denials reveals that Barack Obama gained in support among (potential) voters for whom FEMA aid was approved by the president, while he was not punished for denials of FEMA assistance. We show that this effect is exclusively driven by voters without party affiliation and the that the effect is temporary. – – Für die Regierungen bietet das Auftreten von Naturkatastrophen die Möglichkeit, ihre Bereitschaft und Kompetenz zur schnellen und effizienten Katastrophenhilfe unter Beweis zu stellen. In einer Reihe von Studien wurden die politischen Folgen der Katastrophenhilfe untersucht, indem die Auswirkungen dieser Hilfe auf die nachfolgenden Wahlergebnisse analysiert wurden. Die Ergebnisse dieser Studien führten jedoch zu keinem einheitlichen Ergebnis. Die vorliegende Arbeit leistet einen Beitrag zur bestehenden Literatur, indem sie hochfrequente Umfragedaten zur Zustimmung des Präsidenten verwendet. Die Kombination dieser Daten mit Daten über Waldbrände und Informationen über bewilligte und verweigerte Hilfen bereitgestellt von der Federal Emergency Management Agency (FEMA) zeigt, dass Barack Obama bei (potenziellen) Wählern, denen der Präsident FEMA-Hilfen bewilligte, an Unterstützung gewann, während er bei Verweigerung von FEMA-Hilfen nicht abgestraft wurde. Wir zeigen, dass dieser Effekt ausschließlich von Wählern ohne Parteizugehörigkeit getrieben wird und dass der Effekt vorübergehend ist.
Keywords: 330; Presidential approval; natural disasters; wildfires; disaster aid; disaster declarations; FEMA